Hadith #2477 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Aisha bint Abi Bakr; al-Mqdam bin Shryh bin Han'i المقدام بن شريح بن هانئ بن يزيد; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Sharih bin Hani' al-Harithi شريح بن هانئ (Sunan Abi Dawud)
Abu Sa’id Al Khudri said “A Bedouin asked the Prophet (ﷺ) about emigration. He replied “Woe to you! The matter of emigration is severe. Have you a Camel? He said, Yes. He asked “Do you pay its zakat? He said, Yes. He said, Then work (anywhere) beyond the seas. Allaah will not reduce anything from (the reward of) your work.
Grade: Sahih

Hadith #2555 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; Muhammad bin Rafa'i محمد بن رافع; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي (Sunan Abi Dawud)
Abu Hurairah reported the Apostle of Allaah(ﷺ) as saying “The angels do not accompany the fellow travelers who have a dog or bell (with them).”
Grade: Sahih

Hadith #2888 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Bara' bin Azib bin al-Harith; Mansur bin Abi Mazahim (Sunan Abi Dawud)
The last verse revealed about the decease who left no descendants or ascendants: “They ask thee for the legal decision. Say: Allah directs (thus) about those who leave no descendants or ascendants as heirs.”
Grade: Sahih

Hadith #3375 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Hurairah; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
The Prophet (ﷺ) forbade sale of fruits for a number of years. One of the two narrators (Abu al-Zubair and Sa’id b. Mina’) mentioned the words “sale for years” (bai’ al-sinin instead of al-mu’awamah).
Grade: Sahih

Hadith #3495 - Sunan Abi Dawud - Abdullah bin Tawus عبد الله بن طاوس; Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; ibn Abbas; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade to sell grain which one buys by measurement until one receives it in full.
Grade: Sahih

Hadith #4343 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ady bin 'Ady bin 'Umayra عدي بن عدي بن عميرة; al-Mughira bin Ziyad al-Bjly المغيرة بن زياد البجلي أبو هشام (Sunan Abi Dawud)
When we were around the Messenger of Allah (ﷺ), he mentioned the period of commotion (fitnah) saying: When you see the people that their covenants have been impaired, (the fulfilling of) the guarantees becomes rare, and they become thus (interwining his fingers). I then got up and said: What should I do at that time, may Allah make me ransom for you? He replied: Keep to your house, control your tongue, accept what you approve, abandon what you disapprove, attend to your own affairs, and leave
Grade: Hasan Sahih

Hadith #4641 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Asim al-Ahwal عاصم الأحول; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور (Sunan Abi Dawud)
I heard al-Hajjaj addressing the people say: The similitude of ‘Uthman with Allah is like the similitude of Jesus son of Mary. He then recited the following verse and explained it: “Behold! Allah said: O Jesus! I will take thee and raise thee to Myself and clear thee (of the falsehood) of those who blaspheme.” He was making a sign with his hand to us and to the people of Syria.
Grade: Hasan

Hadith #4944 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
To Allah, his book, his Apostle, the leaders (public authorities) of the believers and all the believers, and the leaders (public authorities) of Muslim and the Muslims and the Muslims in general.
Grade: Sahih